Place-based policies and household wealth in Africa - Matthew Amalitinga Abagna; Cecília Hornok; Alina Mulyukova (University College Dublin, UCD School of Economics, 2024)
This paper provides empirical evidence on the impact of a prominent placebased policy - Special Economic Zones (SEZs) - on the economic well-being of African households. We compile a novel dataset on repeated cross-sections of households living in various distance bands around SEZs in 10 African countries over the period of 1990 to 2020. Exploiting time variation in SEZ establishment, the estimation yields that households in the vicinity of SEZs become significantly wealthier compared to the national average after SEZs are established. The effect is most pronounced for households within 10 km and decays rapidly with distance. We show that this result is not driven by the residential sorting of wealthier households in SEZ neighbourhoods. The rise in wealth is strongest towards the middle of the wealth distribution and goes hand in hand with increased access to household utilities, higher consumption of durable goods, higher levels of education, and a shift away from agricultural activities - patterns that we interpret as indicative of an urbanization trend and the strengthening of the middle class.
Keywords: F6; F21; O15; O25; 330; special economic zone; place-based policy; household wealth; Africa